2009
DOI: 10.1099/vir.0.012575-0
|View full text |Cite
|
Sign up to set email alerts
|

Sorting signals in the measles virus wild-type glycoproteins differently influence virus spread in polarized epithelia and lymphocytes

Abstract: The spread of virus infection within an organism is partially dictated by the receptor usage of the virus and can be influenced by sorting signals present in the viral glycoproteins expressed in infected cells. In previous studies, we have shown that the haemagglutinin (H) and fusion protein (F) of the measles virus (MV) vaccine strain MV Edm harbour tyrosine-dependent sorting signals which influence virus spread in both lymphocytes and epithelial cells to a similar degree. In contrast with the vaccine strain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A second type of signal, a dileucine (LL) motif, has similarly been shown to mediate internalization and targeting of viral glycoproteins to intracellular compartments and to the basolateral surface of polarized epithelial cells (40,41). Mutagenesis of tyrosine and dileucine motifs in the CTs of several other viral envelope glycoproteins provided evidence that they can affect fusion and infectivity (42)(43)(44).…”
mentioning
confidence: 99%
“…A second type of signal, a dileucine (LL) motif, has similarly been shown to mediate internalization and targeting of viral glycoproteins to intracellular compartments and to the basolateral surface of polarized epithelial cells (40,41). Mutagenesis of tyrosine and dileucine motifs in the CTs of several other viral envelope glycoproteins provided evidence that they can affect fusion and infectivity (42)(43)(44).…”
mentioning
confidence: 99%
“…Some early studies of henipavirus fusion demonstrated that the homologous HeV glycoproteins fuse more efficiently than the NiV glycoproteins (Bossart et al, 2002), but it has not been clear why this is the case. Since CDV and NiV attachment protein mutants with cytoplasmic domains of 15 residues or fewer lack tyrosine motifs important for post-translational sorting to the basolateral surface of polarized cells (Moll et al, 2001;Runkler et al, 2009;Weise et al, 2010), the resulting loss of appropriate intracellular transport likely disrupts protein homeostasis and decreases protein expression levels.…”
Section: Disruption Of Niv G Cytoplasmic Signalling Motifs Decreases mentioning
confidence: 99%
“…While the morbillivirus F and H proteins associate early during biosynthesis in the ER and are transported to the cell surface as a complex (Plemper et al, 2001), the henipavirus F and G proteins are transported independently (Whitman et al, 2009), indicating that differences in interactions between glycoproteins may influence the assembly and cell-cell fusion process. Paramyxovirus HN/H/G and F protein cytoplasmic domains also contain tyrosine motifs, which result in transport of proteins to the basolateral surface of polarized cells (Runkler et al, 2009;Weise et al, 2010). These signals, however, are overridden by the homologous matrix (M) protein, resulting in direction of the glycoproteins to the appropriate cellular compartment for virus assembly (Dietzel et al, 2011;Naim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The F and H proteins of measles virus also have tyrosine-dependent sorting signals in the cytoplasmic domains that mediate their targeting to the basolateral site of polarized epithelial cells and facilitate cell-cell fusion between epithelial cells. Transport of measles F and H is not interdependent but each protein traffics alone, as mutation of tyrosines in one protein does not affect localization of the other [186,187]. Additional motifs in cytoplasmic domains that direct basolateral targeting have been identified in non-viral systems, and include the tetrapeptide NPXY motif, dileucine motifs and single leucine residues [188,189].…”
Section: Intracellular Trafficking Of Viral Componentsmentioning
confidence: 99%
“…The paramyxovirus M protein is also considered the main determinant of virus budding sites. Crucial evidence for the central role of M in determination of budding sites was obtained from studies on MeV and NiV, where experiments showed that while the glycoproteins are intrinsically targeted to the basal side of polarized membranes, budding of virus particles occurs at the apical side where the M protein is concentrated, and expression of M during infection partially redirects the glycoproteins to apical surface [150,186,187,195,196,197]. Basolateral sorting of the fusion and attachment proteins can contribute to the pathogenesis of the virus by mediating transmission of viruses to underlying tissues by cell-cell fusion.…”
Section: Intracellular Trafficking Of Viral Componentsmentioning
confidence: 99%